(untitled) (Marketing Journal, 2025)
In this article, food security and its uninterrupted provision in the regions of our country, including the development of fruit and vegetable products and viticulture, which are the main sectors of agriculture, statistical observations and economic and statistical analysis of their development processes, the main aspects of fruit and vegetable production in the field of agricultural problems are described. and ways to overcome them.